Targetting PED/PEA-15 for diabetes treatment. (3rd June 2017) - Fiory, Francesca; Spinelli, Rosa; Raciti, Gregory Alexander; Parrillo, Luca; D'esposito, Vittoria; Formisano, Pietro; Miele, Claudia; Beguinot, Francesco
ABSTRACT: Introduction : PED/PEA-15 is an ubiquitously expressed protein, involved in the regulation of proliferation and apoptosis. It is commonly overexpressed in Type 2 Diabetes (T2D) and in different T2D-associated comorbidities, including cancer and certain neurodegenerative disorders. Areas covered : In mice, Ped/Pea-15 overexpression impairs glucose tolerance and, in combination with high fat diets, further promotes insulin resistance and T2D. It also controls β-cell mass, altering caspase-3 activation and the expression of pro- and antiapoptotic genes. These changes are mediated by PED/PEA-15-PLD1 binding. Overexpression of PLD1 D4 domain specifically blocks Ped/Pea-15-PLD1 interaction, reverting the effect of Ped/Pea-15 in vivo . D4α, a D4 N-terminal peptide, is able to displace Ped/Pea-15-PLD1 binding, but features greater stability in vivo compared to the entire D4 peptide. Here, we review early mechanistic studies on PED/PEA-15 relevance in apoptosis before focusing on its role in cancer and T2D. Finally, we describe potential therapeutic opportunities for T2D based on PED/PEA-15 targeting. Expert opinion : T2D is a major problem for public health and economy. Thus, the identification of new molecules with pharmacological activity for T2D represents an urgent need. Further studies with D4α will help to identify smaller pharmacologically active peptides and innovative molecules of potential pharmacological interest for T2D treatment.